2021
DOI: 10.1038/s41598-021-96956-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing of clinical samples reveals extensively drug resistant tuberculosis (XDR TB) strains from the Beijing lineage in Nigeria, West Africa

Abstract: Multi-drug (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) continues to be a global public health problem especially in high TB burden countries like Nigeria. Many of these cases are undetected and go on to infect high risk individuals. Clinical samples from positive rifampicin resistant Xpert®MTB/Rif assay were subjected to direct whole genome sequencing and bioinformatics analysis to identify the full antibiotics resistance and lineage profile. We report two (2) XDR TB samples also belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…While these studies have demonstrated the feasibility of NGS in TB drug resistance diagnosis, the sequencing platforms are either obsoleted (Colman et al, 2016), or the study only focused on AFB positive specimens with limited variability in drug resistance patterns (Smith et al, 2020). More importantly, as most platform focused on whole genome sequencing data, high-quality genomic DNA prepared from MTB isolates are usually required (Lam et al, 2021;Olawoye et al, 2021). The long turnaround time of MTB culture would not be in favor of rapid MTB resistance analysis.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies have demonstrated the feasibility of NGS in TB drug resistance diagnosis, the sequencing platforms are either obsoleted (Colman et al, 2016), or the study only focused on AFB positive specimens with limited variability in drug resistance patterns (Smith et al, 2020). More importantly, as most platform focused on whole genome sequencing data, high-quality genomic DNA prepared from MTB isolates are usually required (Lam et al, 2021;Olawoye et al, 2021). The long turnaround time of MTB culture would not be in favor of rapid MTB resistance analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the sequencing of drug-resistant tuberculosis strains was performed utilizing Illumina iSeq 100 at Redeemer’s University, in Ede, Nigeria. ( Olawoye et al, 2021 ). The sequencing capacity of North Africa is concentrated in Egypt; for instance, Cairo University (Cairo, Egypt) possesses Illumina MiSeqDx and Ion Proton System, while Suez Canal University (Ismailia, Egypt) exploits Illumina MiSeq.…”
Section: Diagnostic Strategy For the “Ideal Test System”mentioning
confidence: 99%
“…The clinical research trials are still ongoing in Asian [72,73,74,75]and African [76,77,78,79] LMICs to study the sensitivity and specificity of these future-promising techniques with the purpose of including them into national diagnostic methods.…”
Section: (C) Next-generation Sequencing (Ngs)mentioning
confidence: 99%